ASESMEN EUTROFIKASI PERAIRAN PESISIR MENGGUNAKAN METODE INDEKS TROFIK (TRIX) - Hanif Budi Prayitno (OSEANA, 2019)
EUTROPHICATION ASSESSMENT METHOD FOR COASTAL WATER USING TROPHIC INDEX (TRIX). Eutrophication, a process in which water bodies experience excessive growth of aquatic plants due to accumulation of land-originated nutrients especially phosphorus and nitrogen, has become a worldwide coastal environmental problem. Its negative impacts have been well known including oxygen depletion, harmful algal blooms, biodiversity reduction and ecosystem degradation. Unfortunately, the occurrence of those impacts is often not well anticipated as the instruments for assessing the quality of coastal and marine environment are weak and hardly available. Therefore, there has been a growing concern in developing appropriate methods for assessing coastal and marine eutrophication. One of the most widely used methods is trophic index (TRIX) due to its good efficacy. However, it is still questionable whether TRIX is a universal index of eutrophication or the scaling of TRIX should be region specific.